2015
DOI: 10.2495/mc150101
|View full text |Cite
|
Sign up to set email alerts
|

Basalt fibres as a sustainable reinforcement for cement based mortars: preliminary study

Abstract: Considering that uncontrolled construction and inappropriate choices of products are elements that consistently contribute to create a non-sustainable city, this work paid special attention to building science aiming at evaluating basalt fibre as a potential material for eco-compatible constructions. The microstructural and physico-mechanical properties of cement-based mortars reinforced with basalt fibres have been investigated through mechanical (compression and bending) as well as water absorption tests of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Following the analysis involving estimation of the pore structure parameters of the composite using Mercury intrusion porosimeter, thermogravimetric analysis and strength tests, Palou et al [ 46 ] stated that the porosity by crystallization pressure could be enhanced in hardened pastes, which reduce the compression strength. Due to a drop in the strength, Palou et al recommended that the share of fibres in a mortar should be within the approximate range of 0.1%–1.5% of cement weight [ 46 ]. Quattrociocchi et al [ 47 ], who added 1, 3, 6% BF to cement mortars, reported that the dispersion of fibres proved to be more difficult as their content increased in the mixture, which in turn reduced its workability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the analysis involving estimation of the pore structure parameters of the composite using Mercury intrusion porosimeter, thermogravimetric analysis and strength tests, Palou et al [ 46 ] stated that the porosity by crystallization pressure could be enhanced in hardened pastes, which reduce the compression strength. Due to a drop in the strength, Palou et al recommended that the share of fibres in a mortar should be within the approximate range of 0.1%–1.5% of cement weight [ 46 ]. Quattrociocchi et al [ 47 ], who added 1, 3, 6% BF to cement mortars, reported that the dispersion of fibres proved to be more difficult as their content increased in the mixture, which in turn reduced its workability.…”
Section: Discussionmentioning
confidence: 99%
“…According to [ 46 ], in the earlier period of hydrothermal hardening, hydrated products such as C–S–H were formed in the course of a chemical process. Due to the higher crystallization pressure than in the case of non-modified mortars, the porosity of cement mortars increases ( Figure 5 f), simultaneously reducing the compression strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that highest porosity and absorptivity were observed in the cement mortars with the highest amounts of basalt fibers (1.5%), which were 29% and 56% higher than in standard mortar, respectively [65]. Quattrociocchi et al [66] observed that the dispersion of basalt fibers proved to be more difficult, because the workability of the mortars decreased as the amount of basalt fibers increased (up to 6%) in the cement mix. It was necessary to add more water to the mix, thereby increasing the porosity.…”
Section: Discussion On the Physical And Mechanical Properties Of The mentioning
confidence: 97%
“…While the steel of classic armors can corrode through cracks, which may occur when the structural element is subjected to bending and water, oxygen, chlorides, carbon dioxide transport phenomena, basalt ensures good durability both because it's resistant to cementitious environment, and because it is not subject to corrosion phenomena by contaminants. The basalt fiber is also a sustainable material (Quattrociocchi et al, 2015), since its production cycle needs a lower use of primary energy. For each kilo of basalt fiber used instead of the corresponding amount of steel, you can obtain an energy saving of over 9 kWh of primary energy.…”
Section: Performance and Sustainabilitymentioning
confidence: 99%